SHOLAT DHUHA SEBAGAI MEDIA DAKWAH PADA TENAGA PENDIDIK DI UNIVERSITAS SAHID SURAKARTA - Purnomosidi, Faqih (JURNAL TALENTA PSIKOLOGI, 2022)
Da'wah is a practice recommended for every Muslim. There are many media of da'wah that can be used to make individuals know and even close to Islam, one of these media is prayer. Prayer is a practice that can bring many benefits in one's life, both physically and mentally. The prayer referred to in this research is the Duha prayer. The purpose of this study was to identify and describe the description of dhuha prayer as a medium of preaching. The method in this research is qualitative with data collection techniques through interviews and observations. The number of informants in this study amounted to 10 people. The results in this study are that the Duha prayer that the informants do is able to get good happiness, namely the heart becomes calm, at ease, the mind becomes comfortable, the enthusiasm for carrying out work activities, obtaining solutions related to work problems, performance targets become more focused, atmosphere or mood in teaching. more fun and sustenance related to the needs of informants in work matters. With these results, the dhuha prayer has become one of the methods of preaching media in the Sahid University of Surakarta.